ACCOUNTING POLICIES AND FINANCIAL ANALYSIS INTERDEPENDENCES EMPIRICAL EVIDENCE - Nino Serdarević (Economic Review)
This paper presents empirical evidence on applied analysis interdependences with created accounting policies and estimates within Bosnia and Herzegovina (BIH) private commercial entities, in specific, targeting practice oriented relevance of financial indicators, nonfinancial indicators, enterprise resource planning and management account ting insight frequencies. Recently, standard setters (International Accounting Standards Board and International Federation of Accountants) have published outcomes of an internationally organized research on financial reports usefulness, recommending enforced usage of enterprise relevant information, non financial indicators and risks implications in assets and liabilities positions. These imply litigation and possible income smoothening. In regard to financial reporting reliability, many authors suggest accounting conservatism as a measure to compose risk assessment and earnings response ratio. Author argues that recently suggested financial management measures involving cash and assets manage ment,liquidity ratios and turns do not directly imply accounting information quality, prior computed within applied accounting conservatism.